Eco-psychology and the role of animals to heal trauma in life of Pi - Khandar, Diren Ashok; Jujar Singh, Hardev Kaur; Talif, Rosli; Zainal, Zainor Izat (Tarun Tapas Mukherjee, 2020)
Psychological trauma brings about adverse effects on affected victims and the manifestations vary from an individual to another. Some of the more common traits identified in trauma victims include extreme anxiety, nightmares, hallucinations and flashbacks; in which there is no specific reference of time on when a victim may start to exhibit these characteristics. In addition, the mode and duration taken for recovery of psychological trauma may also differ depending on the severity of the initial trauma and assistance available to trauma victims for recovery to transpire. As such, this present article intends to study the varied manifestations of trauma in Yann Martel’s Life of Pi (2001) and to identify how trauma was negotiated through the human-animal relationship formed in the literary text. Besides employing concepts under Trauma theory, this article would also elucidate the concept of ecological unconscious under the lens of Eco-psychology to identify how the incorporation of nature, animals specifically, plays an integral part in the recovery process of a trauma victim.